HUBUNGAN MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN TEKNIK ELEKTRONIKA DASAR SISWA KELAS X JURUSAN TEKNIK AUDIO VIDEO DI SMKN 2 SOLOK - Fachri Ahmad; Sukaya Sukaya; Ahmaddul Hadi (Universitas Negeri Padang, 2015)
The purpose of this study is to reveal the relationship of learning motivation and learning environment on learning outcomes subjects Basic Electrical Engineering class X TAV in SMKN 2 Solok. This research is descriptive correlational. The study population of 60 people and the sample totaled 38 students of class X TAV in SMKN 2 Solok. The sampling technique was randomly (simple random sampling). The data obtained from the results of student learning of subject teachers Basic Electrical Engineering class X TAV in SMKN 2 Solok. While data learning motivation and learning environment were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. Date were analyzed using statistical methods with the help of Microsoft Excel 2007 software. The results showed : ( 1 ) motivation to learn correlates of 10.54 % on the results of class X student TAV in SMKN 2 Solok : ( 2 ) learning environment correlates of 20.56 % on the results of class X student TAV in SMKN 2 Solok ; ( 3 ) learning motivation and learning environment jointly correlated with 21.03% of the results of class X student TAV in SMKN 2 Solok . So it can be concluded that the learning motivation and learning environment correlated to the learning outcomes , the more optimized learning motivation and learning environment , the learning outcomes will be better anyway . Keywords : Learning Motivation , Learning environment , Learning Outcomes, Descriptive correlations , simple random sampling.